Quantum-biological interface in biosensor design: detecting proteins with electrochemical aptasensor - Costa, Leonardo Peres Chiaradia; Batistuti Sawazaki, Marina Ribeiro; Bachour Junior, Bassam; Mulato, Marcelo (Frontiers in Photonics, 2026)
Electrochemical biosensors are promising tools for clinical diagnostics, yet challenges remain in extending sensitivity, linear range, and stability, particularly in complex biological matrices. Here, we report an electrochemical aptasensor for dengue NS1 protein detection based on a self-assembled monolayer (SAM) of DNA aptamers, 6-mercapto-1-hexanol, and 6-ferrocenyl-hexanethiol, characterized using electrochemical capacitance spectroscopy (ECS). The aptamer:thiol ratio was optimized, with the 1:50 condition providing the best analytical performance. The platform achieved sensitivities of 0.18% ± 0.02% per decade in PBS and 0.21% ± 0.01% per decade in commercial human serum, within a linear range of 0.01–1,000 ng/mL. Limits of detection were 24.9 ng/mL in PBS and 25.8 ng/mL in serum. Although long-term stability decreased after 7–14 days, the sensor demonstrated robustness in both simple and complex medium. These results confirm the viability of aptamer-based ECS platforms for clinically relevant NS1 detection and represent a step toward integrating quantum-scale concepts into bioelectrochemical sensing.